An empirical analysis of current zakat collection structures: Implications for the socioeconomic sustainability of the Ummah - Ab Rahman, Siti Maziah; Mohd Zaki, Adeeba Najihah; Wan Muhammad, Wan Mohd Firdaus; Shaari, Rustam (Journal of Islamic, Social, Economics and Development, 2026)
Zakat, as a dynamic Islamic fiscal instrument, plays a critical role in bridging global socioeconomic disparities. This study analyzes the contemporary portfolio structure of zakat collections based on empirical institutional data to assess the most dominant instruments and their implications for sustainable distribution management. Relying on visual composite data from MAIK Dashboard 2026, the findings indicate significant diversification within zakat fund pools. Income Zakat emerges as the largest contributor, closely followed by Business Zakat (RM18,967,776.88) and Zakat Fitrah (RM16,476,878.00). Secondary components such as Zakat on Savings, Shares, Gold/Silver, and Agriculture construct a diversified asset portfolio that solidifies institutional capacity for capital mobilization. Employing a descriptive substantive analysis framework, this study discusses methods to enhance collection via the digitalization of corporate instruments and the application of rigorous governance structures to maximize distribution impact across the eight asnaf groups. The study concludes that integrating financial automation technologies and reforming assessment policies will expand zakat fund spillover effects to achieve inclusive distributive justice.